Nutritional status of Orang Asli (Che Wong Tribe) adults in Krau Wildlife Reserve, Pahang. - Karppaya, Haemamalar; Mohd Shariff, Zalilah; Azman, Neng Azhanie (Nutrition Society of Malaysia, 2010)
This is a descriptive study on nutritional status of Orang Asli (Che Wong tribe) adults in Krau Wildlife Reserve. Twenty-six households, comprising 29 men and 28 women, participated in the study. Dietary diversity was assessed using food frequency questionnaire with 37 food groups. Weight, height and waist circumference were measured using standard instruments. The mean age for men and women was 39.9 ± 17.1 years and 33.7 ± 16.1 years, respectively. Most (89.5%) of the adults had no formal education and about 89.5% of households were categorised as poor. There were 13.8% underweight, 72.4% normal, 10.3% overweight and 3.3% obese men. For women, 25.0%, 46.4%, and 28.6% were underweight, normal and overweight, respectively. While none of the men had at-risk waist circumference (men >90 cm), about 21.4% of women had waist circumference of >80 cm. The mean dietary diversity score was 9.47 ± 4.15 with men (9.48 ± 3.70) and women (9.46 ± 4.63) having similar scores. There was a significant correlation between waist circumference and household income (r=0.36, p<0.01); however, the association was only significant in women (r=0.50, p<0.01). Although under-nutrition still prevails, there are emerging cases of overweight and obesity in this rural Orang Asli community undergoing nutrition transition especially among the females.